Sequence Characteristics and Phylogenetic Analysis of the Artemisia argyi Chloroplast Genome - Chen, Changjie; Miao, Yuhuan; Luo, Dandan; Li, Jinxin; Wang, Zixin; Luo, Ming; Zhao, Tingting; Liu, Dahui (Frontiers in Plant Science, 2022)
Artemisia argyi Levl. et Van is an important Asteraceae species with a high medicinal value. There are abundant A. argyi germplasm resources in Asia, especially in China, but the evolutionary relationships of these varieties and the systematic localization of A. argyi in the family Asteraceae are still unclear. In this study, the chloroplast (cp) genomes of 72 A. argyi varieties were systematically analyzed. The 72 varieties originated from 47 regions in China at different longitudes, latitudes and altitudes, and included both wild and cultivated varieties. The A. argyi cp genome was found to be ∼151 kb in size and to contain 114 genes, including 82 protein-coding, 28 tRNA, and 4 rRNA genes. The number of short sequence repeats (SSRs) in A. argyi cp genomes ranged from 35 to 42, and most of them were mononucleotide A/T repeats. A total of 196 polymorphic sites were detected in the cp genomes of the 72 varieties. Phylogenetic analysis demonstrated that the genetic relationship between A. argyi varieties had a weak relationship with their geographical distribution. Furthermore, inverted repeat (IR) boundaries of 10 Artemisia species were found to be significantly different. A sequence divergence analysis of Asteraceae cp genomes showed that the variable regions were mostly located in single-copy (SC) regions and that the coding regions were more conserved than the non-coding regions. A phylogenetic tree was constructed using 43 protein-coding genes common to 67 Asteraceae species. The resulting tree was consistent with the traditional classification system; Artemisia species were clustered into one group, and A. argyi was shown to be closely related to Artemisia lactiflora and Artemisia montana. In summary, this study systematically analyzed the cp genome characteristics of A. argyi and compared cp genomes of Asteraceae species. The results provide valuable information for the definitive identification of A. argyi varieties and for the understanding of the evolutionary relationships between Asteraceae species.